Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Ex 7.5

Ex 7.5, 1

Ex 7.5, 2

Ex 7.5, 3 Important

Ex 7.5, 4

Ex 7.5, 5

Ex 7.5, 6 Important You are here

Ex 7.5, 7 Important

Ex 7.5, 8

Ex 7.5, 9 Important

Ex 7.5, 10

Ex 7.5, 11 Important

Ex 7.5, 12

Ex 7.5, 13 Important

Ex 7.5, 14 Important

Ex 7.5, 15

Ex 7.5, 16 Important

Ex 7.5, 17

Ex 7.5, 18 Important

Ex 7.5, 19

Ex 7.5, 20 Important

Ex 7.5, 21 Important

Ex 7.5, 22 (MCQ)

Ex 7.5, 23 (MCQ) Important

Last updated at May 29, 2023 by Teachoo

Ex 7.5, 6 Integrate the function (1 − 𝑥2)/(𝑥(1 − 2𝑥)) ∫1▒(1 − 𝑥2)/(𝑥(1 − 2𝑥)) 𝑑𝑥= ∫1▒(1 − 𝑥^2)/(𝑥 − 2𝑥^2 ) 𝑑𝑥 =∫1▒(1/2 + (− 𝑥/2 + 1)/(−2𝑥^2+ 𝑥)) 𝑑𝑥 =1/2 ∫1▒𝑑𝑥+1/2 ∫1▒(−𝑥 + 2)/(−2𝑥^2+ 𝑥) 𝑑𝑥 =1/2 ∫1▒𝑑𝑥−1/2 ∫1▒(𝑥 − 2)/𝑥(1 − 2𝑥) 𝑑𝑥 =1/2 ∫1▒𝑑𝑥−1/2 ∫1▒(𝑥 − 2)/𝑥(2𝑥 − 1) 𝑑𝑥 −2𝑥^2+𝑥 −𝑥^2+𝑥/2 Now Solving (𝑥 − 2)/(𝑥 (2𝑥 − 1) ) = 𝐴/𝑥 + 𝐵/(2𝑥 − 1) (𝑥 − 2)/(𝑥 (2𝑥 − 1) ) = (𝐴(2𝑥 − 1) + 𝐵𝑥)/(𝑥 (2𝑥 − 1) ) Cancelling denominator 𝑥−2=𝐴(2𝑥−1)+𝐵𝑥 Putting x = 0 in (2) 𝑥−2=𝐴(2𝑥−1)+𝐵𝑥 0−2 = 𝐴(2×0−1) + 𝐵×0 −2 = A(−1) …(2) −2 = −𝐴 𝐴 = 2 Similarly Putting x = 1/2 in (2) 𝑥−2=𝐴(2𝑥−1)+𝐵𝑥 1/2 − 2 = A(1/2×2−1)+𝐵×1/2 (−3)/2 = A(1−1)+𝐵×1/2 (−3)/2 = A×0+ 𝐵/2 (−3)/2 = 𝐵/2 𝐵 = −3 Hence we can write it as (𝑥 − 2)/(𝑥 (2𝑥 − 1) ) = 𝐴/𝑥 + 𝐵/(2𝑥 − 1) (𝑥 − 2)/(𝑥 (2𝑥 − 1) ) = 2/𝑥 + ((−3))/(2𝑥 − 1) = 2/𝑥 − 3/(2𝑥 − 1) Therefore , from (1) we get, ∫1▒(1 − 𝑥^2)/𝑥(1 − 2𝑥) =1/2 ∫1▒𝑑𝑥+ 1/2 ∫1▒(2/𝑥 − 3/(2𝑥 − 1)) 𝑑𝑥 =1/2 ∫1▒𝑑𝑥+ 2/2 ∫1▒〖𝑑𝑥/𝑥 −3/2〗 ∫1▒𝑑𝑥/(2𝑥 − 1) =1/2 ∫1▒𝑑𝑥+∫1▒〖𝑑𝑥/𝑥 + 3/2〗 ∫1▒𝑑𝑥/(1 − 2𝑥) =1/2 𝑥+log|𝑥|+3/2 log|1 − 2𝑥|/(−2) +𝐶 =𝒙/𝟐 +𝒍𝒐𝒈|𝒙|−𝟑/𝟒 𝒍𝒐𝒈|𝟏−𝟐𝒙|+𝑪